Lateralizing Asymmetry of Adrenal Imaging and Adrenal Vein Sampling in Patients With Primary Aldosteronism - Wada, Norio (J Endocr Soc, 2019)
CONTEXT: In patients with primary aldosteronism (PA), it remains unclear whether aldosterone-producing adenomas are likely to develop in the left or right adrenal gland. OBJECTIVE: To investigate left-right differences of PA laterality diagnoses via CT imaging and adrenal vein sampling (AVS). DESIGN: Retrospective, observational study. PATIENTS: From the Japan Primary Aldosteronism Study, 1493 patients with PA were enrolled who underwent CT and ACTH-stimulated AVS. MEASUREMENTS: Left or right adrenal nodular lesion distribution and laterality observed on CT scans and from AVS were noted. RESULTS: Both on CT scans and AVS, unilateral results were observed more frequently on the left side than on the right side (25.1% vs 15.4% and 17.3% vs 13.5%, respectively; P < 0.01for both diagnostic techniques). There was no significant difference in the concordance rate for CT and AVS between patients with left and right unilateral nodular lesions observed on CT scans (44.1% and 50.9%, respectively; P = 0.15). In patients with nodules <20 mm, the concordance rate was significantly greater on the right side than the left side (45.8% vs 56.4%; P = 0.03). In patients with bilateral results of AVS, unilateral nodular lesions were detected more frequently on the left side than the right side (17.8% vs 9.4%; P < 0.01). CONCLUSION: These results suggest aldosterone-producing adenomas and nonfunctioning tumors are more likely to develop on the left side in patients with PA and that misdiagnosis of CT-based lateralization may occur more frequently on the left side.